LONG-TERM INDAP THERAPY EFFECTIVENESS AND SAFETY IN ELDERLY PATIENTS WITH ARTERIAL HYPERTENSION - M. E. Statsenko; S. V. Belenkova; T. G. Shcherbakova; O. E. Sporova (Российский кардиологический журнал, 2009)
In total, 40 elderly patients with arterial hypertension (AH) were examined. Seventy percent received indap monotherapy (2,5 mg/d), and 30% – combined therapy (indap plus lisinopril). The follow-up period lasted for 12 months. At baseline and after the end of the treatment, all participants underwent 24-hour blood pressure monitoring (BPM), echocardiography, the measurement of blood lipid profile, glucose, uric acid, and potassium levels, as well as assessment of renal function and quality of life (QoL). After 12 months of indap therapy, stable target blood pressure (BP) levels had been achieved, with reduced mean circadian, mean day-time and mean night-time BP, decreased BP load and morning BP surge rate, but without negative effects of BP variability. Beneficial dynamics of 24-hour BP profile was observed. No negative influences of long-term indap therapy on lipid, carbohydrate, and purine metabolism, as well as on serum potassium levels, were registered. Twelvemonth indap therapy increased elasticity of large vessels, significantly decreased left ventricular myocardial mass, and also improved renal function and QoL in elderly AH patients.